Determinants of the Consumer Bankruptcy Decision - Domowitz, Ian; Sartain, Robert L. (Journal of Finance, 1999)
Qualitative choice models of consumers' decisions to file for bankruptcy and their choice of bankruptcy chapter are estimated jointly, combining choice‐based sampling techniques with a nested estimation procedure. Medical and credit card debt are found to be the strongest contributors to bankruptcy, with homeownership playing an important role with respect to both the decision to declare bankruptcy and the choice of bankruptcy alternative. The potential effects of legal changes relating to property exemptions and dischargeable debt categories are found to encourage debt repayment through Chapter 13.